Strategi Guru Tahfidz Dalam Meningkatkan Hafalan Al-Qur’an Jus 30 pada siswa Kelas II Saudah di Pondok pesantren Imam Safi’i - Rosali, Dian; Wati, Widya; Agustina, Sonia; Afriyani, Een; Nurfaizah, M.M, Enik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies of tahfidz teachers in improving the memorization of the Qur’an Juz 30 among second-grade students as part of the Field Experience Practice (PLP) program at Imam Syafi’i Islamic Boarding School Batam. This research employs a qualitative approach with a descriptive design. The research subjects consisted of one class (second grade) participating in the tahfidz program. Data were collected through observation, interviews, and documentation during the PLP activities. The results show that the strategies applied by the teachers include the talaqqi method, tikrar (repetition), memorization deposit, muraja’ah (review), target setting, motivation, the use of audio media (murottal), and periodic evaluation. The tikrar and muraja’ah methods are proven effective in improving students’ memorization quality due to their structured and continuous implementation¹. In addition, direct interaction between teachers and students has a positive impact on the fluency of memorization². Therefore, appropriate and consistent learning strategies significantly influence the success of the tahfidz program for second-grade students.